DIGITAL MARKETING SEBAGAI STRATEGI MENINGKATKAN PENJUALAN HOME INDUSTRY "PETIS IKAN TONGKOL" - Suhaimi; MABBRUROH, HAJJATUL; Qomariyah, Siti (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2024)
Increasingly competitive business competition makes business actors compete to get attention as a form of maintaining their business. Marketing strategy in social media is a form of marketing effort to achieve high levels of sales volume and profit. The higher level of social media users means that sales opportunities will increase, so this creates opportunities for business actors to be able to develop markets just by holding a smartphone. This is also done by home industry managers in marketing their products, as is currently being done by residents of the South Coast of Tlanakan sub-district who are active as fishermen and home industries processing fish and fish waste. The research method used is descriptive by describing existing and ongoing phenomena. Descriptive research aims to create a systematic, factual and accurate picture of the facts and characteristics of a particular research object. Home industry business owners of tuna fish paste on the south coast of Tlanakan sub-district have used digital marketing as a means of marketing their products. The social media used are Facebook (FB), Instagram (IG), WhatsApp (WA). The big benefit that is most felt by the home industry players in the tuna fish paste on the south coast of Tlanakan sub-district is the intensity of direct communication with customers which is efficient and effective. ease of transactions and displaying product images via community media and information updates all the time so as to increase sales volume all the time.